THE ROLE OF FINANCIAL LITERATURE THROUGH DIGITAL FINANCIAL INNOVATION ON FINANCIAL INCLUSION (CASE STUDY OF MSMES IN SALATIGA CITY) - Dewi Widyaningsih; Edy Siswanto; Edwin Zusrony (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research conducted analyzes the effect of the relationship between financial literacy and the accessibility of digital financial innovation on financial inclusion, financial literacy on digital financial innovation and moderating the relationship between financial literacy and financial inclusion through digital financial innovation. The study used a non-random sampling technique that was taken as many as 40 MSME actors and the technique of distributing questionnaires was convenience sampling. Completion of the multiple linear regression model and the Moderated Regression Analysis (MRA) interaction test. The results obtained that financial literacy and accessibility of digital financial innovations have a significant effect on financial inclusion, financial literacy has a significant effect on digital financial innovation. The research findings show the high level of financial literacy of the community and MSME actors as well as digital and financial technology literacy behaviors and attitudes, making it easier to promote the use of digital financial innovation products so that they can expand financial inclusion. Meanwhile, digital financial innovation information does not have a direct role in mediating the relationship between financial literacy and financial inclusion.